IMPROVING SPEAKING SKILL OF REPORT TEXT USING FINDING MISSING INFORMATION TECHNIQUE AT THE TENTH GRADE STUDENTS OF MA SHABILAL HUDHA SUNGAI EMPAT - Ana Setiawati; Melda Yeni; Sri Erma Purwanti (J-Shelves of Indragiri (JSI), 2020)
This study aims at improving students' speaking skills in using English with the approach of finding missing information techniques in the report text in the tenth grade of MA Shabilul Hudha Sungai Empat. In learning English, especially those that focus on their learning abilities, making these they become brave enough to express or not dare to use and communicate using English is because they feel ashamed of their classmates and their habit of using mother tongue conversation. This research is a classroom action research, where the implementation time is one month or four meetings starting from April 13, 2019, to April 24, 2019, with participants in the tenth grade MA Shabilul Hudha Sungai Empat totaling 30 students in the data collection process; the researcher used tests to students in the form of report texts and the form of observations of students and teachers. The field data analysis results obtained students' value in the first cycle test with an average value of 68.07, so this study used two cycles for the assessment of students' speaking skills. In the second cycle test, the average score was 75.84; in other words, the study using learning methods finding missing information techniques to improve the speaking skills of tenth graders Shabilul Hudha Sungai Empat can improve students' speaking skills. Therefore, using learning methods to find missing information techniques is useful for improving students' speaking skills.